Effect of intracellular vesicular stomatitis virus mRNA concentration on the inhibition of host cell protein synthesis. - Schnitzlein, W M (1983)
Inhibition of host cellular protein synthesis by vesicular stomatitis virus (VSV) has been suggested to be primarily the result of competition for ribosomes between cellular and viral mRNAs (H. F. Lodish and M. Porter, J. Virol., 36:719-733, 1980; Lodish and Porter, J. Virol. 38:504-517, 1981). This hypothesis was investigated by regulating the extent of VSV mRNA synthesis through the use of defective interfering particles. Although intracellular VSV mRNA concentrations decreased by as much as a factor of 14 at high multiplicities of infection of defective interfering particles, the inhibition of host cell protein synthesis by VSV decreased by a maximum of only 10%. The data also indicated that under these conditions the protein-synthesizing capacity of the cells was not exhausted. We concluded that competition for cellular ribosomes could not have been the major factor in the inhibition of host cell protein synthesis by VSV. This conclusion was further supported by inhibition data obtained with VSV mutants. The ts G22 mutant, defective in replication but not in primary transcription, inhibited host protein synthesis at the nonpermissive temperature (39 degrees C) to the same extent as did wild-type virus, even though it generated only 30 to 50% of the amount of viral mRNA as did wild-type virus. Conversely, in infections with the R1 mutant, which did not inhibit host cell protein synthesis, the amount of total and polysome-bound viral mRNA was indistinguishable from that obtained in infections by wild-type virus.